Efficiency Wages, Urban Unemployment and Housing Consumption - Yves Zenou (The Research Institute of Industrial Economics (IUI), 2003)
The aim of this paper is to introduce endogenous housing consumption in an efficiency wage model in which two cases are considered: very high and zero relocation costs. First, in both cases, we are able to totally characterize the efficiency wage for any preferences that are quasi-linear with respect to the composite good consumption. Second, in each case, we show how endogenous housing consumption affects the value of the efficiency wage (compared to the case of fixed housing consumption) and demonstrates the existence and the uniqueness of a steady-state equilibrium. Finally, we compare the two models and show how mobility costs affect the efficiency wage setting.
Keywords: J41; R14; 330; Relocation Costs; Location-Dependent Wages; Urban Labor Markets; Städtische Arbeitslosigkeit; Städtischer Arbeitsmarkt; Wohnkosten